50.8k views
1 vote
1

Solve for x: (2x - 1) + (4x + 9) = 32 m
O x = 40/6
O x = 4
x = 22/6
Other

2 Answers

5 votes

Answer:

2x -1 + 4x +9 =32

=) 6x +8 =32

=) 6x ==32-8

=) 6 x = 24

=) x = 24/6

=) x = 4

User Shakeima
by
5.0k points
5 votes

Answer:


x = (40)/(6)

Explanation:

To solve the equation

(2x - 1) + (4x + 9) = 32

First of all remove the parenthesis

That's

2x - 1 + 4x + 9 = 32

Simplify

We have

6x - 8 = 32

Add 8 to both sides

Thats

6x - 8 + 8 = 32 + 8

6x = 40

Divide both sides by 6

That's


(6x)/(6) = (40)/(6)

We have the final answer as


x = (40)/(6)

Hope this helps you

User Belvederef
by
4.9k points